Mycobacterium neoaurum Bacteremia in an Immunocompetent Patient in MICU: The First Reported Case in Qatar - Alanoud Alshmarri; Noor Jasim; Hisham Elhiday; Bara Alqudah (Case Reports in Infectious Diseases)
Conclusion: This is the first documented case of Mycobacterium neoaurum bacteremia in Qatar and one of the few reported cases globally in an immunocompetent patient without conventional risk factors.